Pattern of clinico-haematological presentation of newly diagnosed adult aplastic anaemia in Bangladesh - Motaleb, Abdul; Khan, Mohammad Abdullah Az Zubayer; Ahmed, Alamgir; Khatun, Alam Ara (International Journal of Research in Medical Sciences, 2024)
Background: Aplastic anaemia (AA) is characterized by pancytopenia and a hypocellular bone marrow without abnormal infiltrates. While commonly seen in young adults, there is a secondary peak of incidence in the fifth and sixth decades of life. This study aimed to assess the clinical presentation and haematological profiles of adult AA patients in Bangladesh. Methods: A cross-sectional study was conducted on 49 newly diagnosed adult AA patients at the Department of Haematology in Bangabandhu Sheikh Mujib Medical University (BSMMU) from September 2014 to March 2015. Results: The average age of patients was 36 years (±15), with a range of 18 to 77 years. Nearly half (45%) were aged 18-30 years, and the male-to-female ratio was 2.8:1. Anaemia (100%), fatigue (92%), fever (84%), and respiratory distress (73.5%) were the most frequent symptoms. Bleeding was present in 65%, with petechiae (49.2%) and ecchymosis (29.2%) being the most common. Among 19 patients who were tested for hepatitis, 36.8% were positive for hepatitis B virus. All patients had pancytopenia, hypocellular bone marrow, and decreased megakaryopoiesis. Reduced erythropoiesis was observed in 83.7%. Haemoglobin, total WBC, absolute neutrophil, and platelet counts were reduced, while lymphocyte counts were elevated. Conclusions: Aplastic anaemia is a significant cause of pancytopenia. Accurate diagnosis requires comprehensive clinical evaluation and haematological testing. Differentiation from inherited bone marrow failure syndromes, such as Fanconi anaemia, necessitates advanced tests like chromosomal breakage studies and karyotyping.